Monovalent 'Features' in Phonology. Issue 2 (February 2016) - van der Hulst, Harry
Abstract : In this article, I discuss and review the proposal to replace traditional binary features (such as [+round]) by unary, single‐valued, or monovalent units (such as |round|). I will focus on proposals within the context of dependency phonology, government phonology, and radical CV phonology . In all three approaches, in addition to unary primes, use is made of head–dependency relations . The central motivation for switching from a binary to a unary understanding of phonological primitives comes from the empirical finding that binary approaches wrongly predict that both values of each feature define natural classes of segments or can be involved in a process. The central idea behind monovalency is that in all cases, only one pole of a phonetic opposition can play these roles. A monovalent approach is thus inherently more restrictive and therefore should form the null hypothesis.